2022
DOI: 10.21037/hbsn-21-45
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score matching study of 325 patients with spontaneous rupture of hepatocellular carcinoma

Abstract: Background: This study aims to find out the possible optimal therapy and assess the prognosis properly for patient with spontaneous rupture of hepatocellular carcinoma (HCC).Methods: Propensity score matching (PSM) analysis was used to study the data from 325 patients with ruptured HCC (RHCC) and 2,291 patients with non-RHCC.Results: The incidence and hospital mortality of RHCC were 5.1% and 0.8% respectively, with a median overall survival (OS) time of 17 months. There was no difference between ruptured and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
0
17
2
Order By: Relevance
“…However, this outcome remains significantly worse than that observed in treated HCC cases. 3,24 Liver failure significantly contributes to mortality in patients with SRHCC and is particularly linked to increased short-term mortality rates. 25,26 Our findings indicate that 63.1% of patients experiencing ALF died within one month, and the one-year survival rate was a mere 8.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this outcome remains significantly worse than that observed in treated HCC cases. 3,24 Liver failure significantly contributes to mortality in patients with SRHCC and is particularly linked to increased short-term mortality rates. 25,26 Our findings indicate that 63.1% of patients experiencing ALF died within one month, and the one-year survival rate was a mere 8.7%.…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have reported a decline in mortality rates, it remains a challenging issue within the realm of hepatobiliary surgery. [3][4][5][6][7] Acute liver failure (ALF) frequently contributes to mortality in end-stage liver disease, a trend similarly observed in patients with SRHCC. 5,8 During the acute phase of the disease, ALF incidence ranges from 12% to 42%.…”
Section: Introductionmentioning
confidence: 95%
“…Hepatocellular carcinoma (HCC) is the sixth most common and the third most deadly malignant tumor in the world [ 1 ]. Although HCC tumors spontaneously rupture in fewer than 3% of patients in the West, rupture occurs in 2–26% of patients in Asia [ [2] , [3] , [4] , [5] , [6] , [7] ]. Studies have found that even if ruptured HCC patients can be managed promptly in the event of a critical situation, their long-term prognosis is worse than that of non-ruptured HCC [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death in Asian and African countries due to a high prevalence of chronic hepatitis B infections ( 1 , 2 ). The vast majority of current studies focus on the treatment of HCC itself rather than complications from HCC.…”
mentioning
confidence: 99%